Provider Responses to the Expansion of Public Subsidies in Healthcare: The Case of Oral Chemotherapy Treatment in Australia - Maryam Naghsh Nejad; Serena Yu; Philip Haywood (Institute of Labor Economics (IZA), 2023)
We examine provider responses to the expansion of public subsidies in 2015 for oral chemotherapy treatment, in a health system where providers were free to determine their own prices. Oral chemotherapy treatment was known to have similar efficacy to its traditional intravenous alternative and was preferred by patients for its at-home administration. However, from a policymaker's perspective, the potential for misalignment between patient and provider preferences was significant given the shift to full reimbursement for the oral chemotherapy medication but no change in fee-for-service payments for associated chemotherapy services. Under this scenario, a shift away from traditional intravenous chemotherapy may entail reduced activity and revenues associated with infusions for providers, and we hypothesise that it may result in unintended policy consequences such as reduced take-up of oral chemotherapy or higher prices. We implement a difference-in-difference model using national administrative data on services provided, and chemotherapy medications prescribed, by providers to 1850 patients in New South Wales, Australia. Our estimates indicate that the subsidies expanded access to oral chemotherapy for newly eligible patients by 15 percentage points. However, prices charged by providers for an episode of care rose by 23 percent, driven mostly by increases in service volumes. The results illustrate the importance of understanding differential provider responses to policy changes in financial incentives.
Keywords: I11; I13; D04; 330; provider behavior; financial incentives; applied microeconomics